2020
DOI: 10.4269/ajtmh.19-0726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Face Washing and Face Wiping Methods for Trachoma Control: A Pilot Study

Abstract: Eye-to-eye transmission of Chlamydia trachomatis, the causative agent of trachoma, may be plausibly interrupted if faces are kept free of ocular and nasal discharge. Between April and June 2018, 83 children aged 1-9 years with active trachoma were recruited from 62 households and allocated to a face cleaning protocol: face washing with water, face washing with water and soap, or face wiping. Faces were examined for the presence of ocular and nasal discharge, and swabs were taken from faces and hands to test fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…By the end of the study, face-washing with soap had become much more common in the intervention clusters than the control clusters, an encouraging sign since soap has been found to play a key role in clearing ocular discharge and ocular chlamydia. 28 Practise of the main hygiene message – face-washing with soap twice a day – was also more common in intervention clusters, although this practice was reported by only 26–43% of participants by month 36. These results, while affirming the challenges inherent in behavioural interventions, nonetheless point to positive changes in face-washing during the study period.…”
Section: Discussionmentioning
confidence: 98%
“…By the end of the study, face-washing with soap had become much more common in the intervention clusters than the control clusters, an encouraging sign since soap has been found to play a key role in clearing ocular discharge and ocular chlamydia. 28 Practise of the main hygiene message – face-washing with soap twice a day – was also more common in intervention clusters, although this practice was reported by only 26–43% of participants by month 36. These results, while affirming the challenges inherent in behavioural interventions, nonetheless point to positive changes in face-washing during the study period.…”
Section: Discussionmentioning
confidence: 98%
“…The target for facial cleanliness is having a clean face, at any time of day [ 26 , 27 ]. The facial cleanliness indicators used in this study indicate that this was not achieved, and highlight the importance of continued face washing throughout the day.…”
Section: Discussionmentioning
confidence: 99%
“…The facial cleanliness indicators used in this study indicate that this was not achieved, and highlight the importance of continued face washing throughout the day. In a pilot study comparing face washing and wiping methods, Czerniewska et al [ 27 ] observed that the impact of washing with soap was sustained for four hours for ocular discharge, and was limited and not sustained for nasal discharge. Similarly, King et al [ 8 ] observed that by four hours post-face washing, the presence of ocular and nasal discharge was no longer able to predict whether the face had been washed or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the trachoma-protective effect of keeping children's faces free of ocular and nasal secretions [6][7][8][9][10][11][12][13][14]. Washing faces as often as needed is apparently a crucial way to keep faces clean; current educational programs focus on the importance of face-washing [15][16][17][18][19][20][21]. However, further work to evaluate additional factors that influence facial cleanliness is needed.…”
Section: Introductionmentioning
confidence: 99%